Agro-ecological approach to combat climate change impact - Dwivedi, B S; Patil, N G (Indian Farming, 2023)
The Observer Research Foundation report (2023) states that, “India, an emerging economy, ranks first among all G20 members in terms of overall climate performance, owing to its significantly low per capita contributions to carbon and GHG emissions; very limited share in legacy emissions relative to its population needs; least rate of per capita energy use; and significant efforts towards, not only preserving, but also expanding its climate-regulating land cover by 6% compared its 1992 levels. India has also done well in climate policy initiatives and limiting the unbridled expansion of climate-altering land cover.” Such reports are generated with the help of: (a) baseline data from different systematically categorized regions/zones, (b) studies on how climatic aberrations affect agriculture, and (c) how such regions/zones respond to, and offset the effects of climate change.